1994
DOI: 10.1038/ki.1994.74
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed antibody and interleukin-6 responses to acute pyelonephritis in pregnancy

Abstract: This study examined the effect of pregnancy on the host response to acute pyelonephritis. Urine and serum samples were obtained at the time of diagnosis and after two weeks, from non-pregnant and pregnant women with acute pyelonephritis. The samples were analyzed for interleukin-6 (IL-6) and specific antibody activity to antigens extracted from the Escherichia coli strain infecting each patient. The host response to infection was further quantitated as fever, C-reactive protein, and renal concentrating capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Depending on this result there was significant correlated between study group and mannose binding lectin Polymorphism. The result was agreement with result obtained by 10 who were observed a correlation between the maternal high mannose binding lectin genotype A and premature birth, and it was suggest that during pregnancy mannose binding lectin-associated inflammation caused by higher mannose binding lectin activity may lead to earlier delivery. Moreover, this result finding explain why some peoples are mannose binding lectin deficient in the general population.…”
Section: Resultssupporting
confidence: 92%
“…Depending on this result there was significant correlated between study group and mannose binding lectin Polymorphism. The result was agreement with result obtained by 10 who were observed a correlation between the maternal high mannose binding lectin genotype A and premature birth, and it was suggest that during pregnancy mannose binding lectin-associated inflammation caused by higher mannose binding lectin activity may lead to earlier delivery. Moreover, this result finding explain why some peoples are mannose binding lectin deficient in the general population.…”
Section: Resultssupporting
confidence: 92%
“…pregnancy is accompanied by lower levels of IL-6 in serum and urine compared with those in nonpregnant women suffering from pyelonephritis [76]. IL-6 and IL-8 were also detected for up to 6 weeks in the urine of children with acute pyelonephritis [77].…”
Section: Inflammatory Response To Urinary Tract Infectionmentioning
confidence: 96%
“…An interesting aspect of pregnancy is a relative status of immunosuppression, presumably due to the presence of the "foreign" genome of the fetus. Petersson et al (101) reported significant decline in the immune response in pregnant subjects to acute pyelonephritis. That is, maternal serum and urine interleukin-6 and specific antibody responses to E. coli were diminished in comparison to the situation in their non-pregnant counterparts at diagnosis.…”
Section: Urinary Tract Infection In Pregnancymentioning
confidence: 99%